New implementation of the abstract design for non-iterative hash functions with 1024 digest length NIHF-1024 - Abouchouar Abdallah; Fouzia Omary (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
The non-iterative hash function design is a domain extension that uses a novel concept to fill a gap in existing cryptographic designs. This design avoids the structural issues that plagued prior paradigms, particularly those applying the Merkel-Damgârd design, by presenting a novel approach. Non-iterative hash function design, on the other hand, is an abstract idea that necessitates the specification of the internal transformation in order to test and experiment it. To achieve this goal, this article describes the algorithm that implements the internal transformation based on the main characteristics of the new model. The avalanche effect's results are provided in the experiment section, as well as a preliminary validation stage of the national institute of standards and technology (NIST's) cryptographic algorithm validation program (CAVP), which employs a set of test vectors to verify algorithm accuracy and implementation errors.